Combining technical and business studies at the Universidad Politécnica de Madrid: Analysis of the Double Degree student profile - Irene Blanco-Gutierrez; Paloma Esteve; Sergio Zubelzu (Advances in Building Education, 2022)
Double degrees have emerged as an attractive alternative for Spanish university students. The Double Degree in Building and in Business Administration and Management (EDIF-ADE) was a pioneer among the Double Degrees implemented at the Universidad Politécnica de Madrid (UPM) and is currently experiencing a great demand. This study analyses the profile of EDIF-ADE students to understand the keys to this success. Through a survey of first-, second-, third-, and fourth-year students, we examined (1) students’ prior knowledge; (2) motivations and interest areas; (3) educational and occupational expectations; (4) results and knowledge acquired. The results of the study reveal that, although most of the students had no prior knowledge of economics and business, they consider this training as an important element in their future professional development that enhances their employability prospects.